2016
DOI: 10.18203/issn.2454-2156.intjscirep20160503
|View full text |Cite
|
Sign up to set email alerts
|

Small bowel volvulus: a rare twist in an adult

Abstract: <p class="abstract"><span lang="EN-US">Volvulus is a special form of mechanical intestinal obstruction. It is most commonly seen in sigmoid colon. It results from abnormal twisting of a loop of bowel around the axis of its own mesentery. Small bowel volvulus (SBV) is a rare condition even though the incidence in Africa and Asia is high. It is of two types; primary and secondary. It requires emergency surgical intervention; more so as consuming time increases the risk of bowel getting gangrenous. He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…We found that primary SBV accounted 100% of SBV. The presumed risk factors in different literature were hypermobility of bowel gut, hypermobility of mesentery, and bulky and poorly digestible diet taken at long intervals [2,7,9,17].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that primary SBV accounted 100% of SBV. The presumed risk factors in different literature were hypermobility of bowel gut, hypermobility of mesentery, and bulky and poorly digestible diet taken at long intervals [2,7,9,17].…”
Section: Resultsmentioning
confidence: 99%
“…Diet and pattern of feeding is also the most relevant risk factor for occurrences of primary SBV. The Abrupt change of dietary habit of ingestion of a single large amount and bulky food after a long interval of fasting or empty of bowel may induce forceful bowel peristalsis, resulting in SBV [ 2 , 7 , 9 , 17 ]. Secondary small bowel volvulus occurs in the presence of underlying identified predisposed conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The most common procedure for non-respond for conservative measures were derotation and milking (DAM) for 39.9% and primary resection and anastomosis for 16.2 %( Table3). The overall morbidity rate was 5.4% (N=8) and the mortality rate was 3.4 %( N=5) ( June 1992toMay 19961992toMay 19801992toMay -19901992toMay 19751992toMay -19841992toMay 19651992toMay -19801992toMay 19621992toMay -1965 Duration of bowel gut, hypermobility of mesentery, and bulky and poorly digestible diet taken at long intervals [2,7,13,17].…”
Section: Resultsmentioning
confidence: 99%
“…Diet and pattern of feeding is also the most relevant risk factor for occurrences of primary SBV. The Abrupt change of dietary habit of ingestion of a single large amount and bulky food after a long interval of fasting or empty of bowel may induce forceful bowel peristalsis, resulting in SBV [2,7,13,17]. Secondary small bowel volvulus occurs in the presence of underlying identi ed predisposed conditions.…”
Section: Resultsmentioning
confidence: 99%
“…The morbidity rate was 5.4% (N = 8) and the Mortality rate was 3.4%( N = 5) ( Table 1).We found that primary SBV accounted 100% of SBV. The presumed risk factors in different literature were hypermobility of bowel gut, hypermobility of mesentery, and bulky and poorly digestible diet taken at long intervals [2,7,13,17]. 1992toMay 19961992toMay 19801992toMay -19901992toMay 19751992toMay -19841992toMay 19651992toMay -19801992toMay 19621992toMay -1965 Duration Years The speculation was some populations have long mesenteric and short roots of mesentery which would allow abnormal mobility of whole or segment of the small bowel.…”
Section: Ethical Considerationmentioning
confidence: 99%